The model of voter education of women-based democracy volunteers - Hambali, Hambali; Hariyanti, Hariyanti; Eddison, Ahmad (Universitas Negeri Yogyakarta, 2021)
This study aimed at describing the model of voter education of women-based democracy volunteers in Pekanbaru City and Dumai City. Democracy volunteers are partners in the General Election Commission, who deliver electoral information to the public. The voter education model consists of the strategies used, the material delivered, the methods used to provide knowledge, raise awareness, and increase women voters' political participation. This research employed a qualitative approach with descriptive methods